Accommodation intersubjective et générique dans le forum du Madman’s Café - Stéphane Kostantzer (Anglophonia)
The forum of The Madman’s Café is a place where a community of fans unite in order to engage in in-depth conversations about the latest in Japanese pop culture. Integration into such a selective community requires exacting efforts of accommodation, compelling the members to conform to the generic norms of this particular forum, which derive from the figure of a clearly identifiable prototypical member. Our hypothesis is that, in the exchanges, generic accommodation takes precedence over intersubjective accommodation, which will undoubtedly pose a problem for the expression of identity.In line with Giles’ theories, accommodation is broken down into four subtypes, whether it describes a movement of convergence or divergence, and whether this movement is predominantly ideological or stylistic in kind. Close attention to the observable linguistic material reveals the multiple strategies that contributors use in order to converge toward the generic norms of this forum all the while expressing their identity via necessary divergences. The main strategy for the contributors to differentiate consists of embedding other genres (in the Bakhtinian sense of the word) in their messages, sometimes affiliated, sometimes totally unrelated to the norms of this forum, from which the speakers may diverge inconsequentially, or towards which they may feign a useless convergence—a process that has strong humorous potential. Humour, which generally proceeds from an intentional hiatus between a stylistic convergence and an ideological divergence, is a vehicle of choice for the expression of one’s personal identity. Even better, not only does humour allow divergence, it in fact legitimizes it: as the name of the site suggests, this forum, however elitist it may be, inscribes inventiveness at the heart of its generic identity. Humour thereby also entertains the members’ social identity, as the study of our corpus demonstrates. The corpus illustrates three different types of thread: an on-topic thread, an off-topic thread, and a first-contribution thread.